Dysphagia related quality of life (QoL) following total laryngectomy (TL) - Georgiou, Anastasios M.; Kambanaros, Maria (My University, 2017)
Purpose: This cross-sectional study evaluated the relationship between dysphagia post-total laryngectomy (TL) and quality of life (QoL) of people who reside in Greece. This is the first such report to be undertaken on the topic. Methods: Speech and language therapists typically use patient judgement to identify difficulties with swallowing. The Greek adaptations of the M.D. Anderson Dysphagia Inventory (MDADI) and the Eating Assessment Tool (EAT-10) were completed by members of the Hellenic Association of Laryngectomees (HAL). More than 400 questionnaires were sent, but only 23 were returned (18 males and 5 females). Results: The results revealed that dysphagia has a negative impact on the QoL of people who have undergone TL for treatment of laryngeal cancer. Conclusion: It appears that not only treatment (i.e. TL) of the primary disease, but also secondary problems as a result of the treatment, such as dysphagia, have a significant impact on the QoL of patients and must be taken into consideration when therapeutic decisions for laryngeal cancer are made. The qualitative measures used here provide a starting point to objectively describe QoL as perceived by TL patients. This is particularly pertinent in Greece where access to delivery and quality of health services has been challenging because of recent fiscal constraints.
Keywords: Deglutition disorders; Laryngeal cancer; Laryngectomy